A imagem da polícia militar no município de Macapá: estudo de caso dos bairros Zerão, Universidade e Central, no ano de 2014 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2014)
The work aims to analyze the image of the Military Police of Amapá and the variables that influence it, from the perspective of residents of neighborhoods Center, Zerão University and the city of Macapa (state of Amapá ) , in 2014.For data collection was used to interview technique, using as a previously designed and tested questionnaire containing closed questions. Thus, it appears that many problems at work PMAP: indifference in addressing the occurrences and inefficiency; lack of professional training ; poor professional training.This reflects a growing sense of insecurity on the part of residents, which makes disapprove of how the work is executed by the PMAP.
Keywords: Percepção; Imagem; Polícia Militar do Estado do Amapá; Insegurança; CNPQ::CIENCIAS SOCIAIS APLICADAS